Current Problems and Solutions in The Educational System - Masharipova Sarvinoz Alisher qizi (Web of Journals Publishing, 2023)
Education is an important aspect of human development, it is the fundamental right of each person.Education is seen as the key to development and change in any society, since it plays a decisive role in the formation of individuals, communities, societies and the whole world./ Despite the huge achievements in the field of education on a global scale, in particular in the last century, several problems are hindering its effectiveness and effectiveness. This article discusses the main problems facing the education system today and offers solutions to help solve them.
Keywords: Funding, academic quality, student engagement, standardized testing, technology integration, resource utilization, educational equity, pedagogy, and educational policy.